2011
DOI: 10.1177/1741826711398432
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate recovery, exercise capacity, and mortality risk in male veterans

Abstract: HRR at 2 min post exercise is strongly and inversely associated with all-cause mortality. Exercise capacity affects HRR-associated mortality substantially and should be considered when applying HRR to estimate mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…Still, few studies were carried out in order to understand the interaction between HRR measures, aerobic fitness and mortality. In a pioneering study, Kokkinos et al 33 , evaluating the association between HRR (1 st and 2 nd min of recovery), aerobic fitness and risk of mortality from all causes in a cohort of 5,974 men with a follow-up period of 6.2 years, showed that in individuals with low aerobic fitness and low HRR, the mortality risk was approximately seven times higher when compared to subjects with good aerobic fitness and high HRR. The authors emphasize that the aerobic fitness associated with HRR substantially affects mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Still, few studies were carried out in order to understand the interaction between HRR measures, aerobic fitness and mortality. In a pioneering study, Kokkinos et al 33 , evaluating the association between HRR (1 st and 2 nd min of recovery), aerobic fitness and risk of mortality from all causes in a cohort of 5,974 men with a follow-up period of 6.2 years, showed that in individuals with low aerobic fitness and low HRR, the mortality risk was approximately seven times higher when compared to subjects with good aerobic fitness and high HRR. The authors emphasize that the aerobic fitness associated with HRR substantially affects mortality.…”
Section: Discussionmentioning
confidence: 99%
“…First, the methods of HRR 2 assessment have included using a passive recovery period, with the participants placed supine immediately after peak exercise, 14,21,23,25,26,43 immediately seated, 18,41,50,70 or standing for 2 minutes and then seated for several minutes. 44 The methods using an active cooldown recovery have included walking at 1.5 mph and at 2.5% grade for 2 minutes 15,17,20,42 or at a speed of 1 mph for 1 minute. 12 Second, HRR has been examined during a range of minutes into recovery.…”
Section: Discussionmentioning
confidence: 99%
“…929 Poor ANS control of the CVS system is a plausible mechanism underlying the factors associated with attenuated HRR and increased risk for cardiac events and mortality. The preponderance of HRR research has focused on apparently healthy individuals, 18,30 men, 1316,20,21,29 or patients with heart failure (HF). 22,3137 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical exercise tolerance tests (ETTs) to quantitatively assess cardiorespiratory fitness (CRF) and heart rate recovery (HRR) post-exercise can improve risk stratification [3][5], but the expense of testing large populations [6], [7] and low primary care utilization rates in young adults [8] limits clinical efforts for early risk detection. Exercise field tests (EFTs) completed while wearing commercial heart rate monitors (HRMs) may provide an inexpensive alternative for risk assessment in large populations, but improved CRF prediction models and validation of HRR measures are needed.…”
Section: Introductionmentioning
confidence: 99%